Glasoslovje prekmurskega govora Cankove skozi čas - Jakop, Tjaša (Slavia Centralis, 2025)
The Phonetics of the Cankova (Prekmurje) Dialect over Time. This paper presents and describes the local dialect of Cankova, which according to Slovenian dialectology belongs to the Ravensko-Goričko local dialect of the Prekmurje region that adheres to the Pannonian dialect group. The dialect material for this article was collected in Cankova (data-point SLA T387) according to the questionnaire for the Slovenian Linguistic Atlas (SLA) and has been compared to older dialect material from the same village, published in 1909 in Avgust Pavel’s detailed description of the phonology of the Cankova (Prekmurje) dialect. The phonetics and phonology of this local dialect are presented in the article in greater detail.
Keywords: dialectology; Pannonian dialect group; Prekmurje dialect; Ravensko-Goričko sub-dialect; phonetics and phonology; Cankova; Avgust Pavel